Metformin exposure and survival in head and neck cancer: A large population‐based cohort study. (14th February 2019) - Alcusky, Matthew; Keith, Scott W.; Karagiannis, Tom; Rabinowitz, Carol; Louis, Daniel Z.; Maio, Vittorio
Summary: What is known and objective: Observational clinical studies of metformin for prevention and treatment of several cancer types have reported mixed findings. Although preclinical studies have suggested metformin may reduce head and neck cancer (HNC) proliferation, clinical evidence is limited. The objective of this large population‐based study was to evaluate the relationship between metformin exposure following HNC diagnosis and all‐cause mortality. Methods: We conducted a retrospective cohort study using the Italian Emilia‐Romagna Regional administrative healthcare database, which includes demographic, hospital and outpatient prescription information for ~4.5 million residents. Included patients were followed from the first hospital discharge (index) during the study period (01/2003‐12/2012) with a diagnosis of HNC. Metformin exposure and select covariates were operationalized in a time‐dependent manner during follow‐up. Cox proportional hazards models estimated the covariate‐adjusted time‐dependent association between metformin exposure and all‐cause mortality. Results and discussion: Among 7872 patients diagnosed with HNC, 708 (9.0%) were exposed to metformin after HNC diagnosis, and 3626 (46.1%) died during follow‐up (median follow‐up: 35.2 months). In the covariate‐adjusted model, the all‐cause mortality rate appeared lower (HR: 0.81, 95% CI: 0.61‐1.09) among metformin exposed patients during the 2 years post‐diagnosis, while the all‐cause mortality rate appeared higher (HR: 1.20, 95% CI: 0.94‐1.53) among exposed patients after 2 years post‐diagnosis. Metformin was protective among patients ≤60 years of age (HR for the period of 0‐2 years post‐diagnosis: 0.22, 95% CI 0.09‐0.56; HR for the period ≥2 years post‐diagnosis: 0.56, 95% CI 0.26‐1.22) but not in those >60 years. What is new and conclusion: In this population‐based study of metformin in HNC, we found a modest protective association between metformin exposure and all‐cause mortality in the 2‐year post‐diagnosis period. Age appeared to modify the association between metformin and HNC survival. Abstract : In this population‐based study of metformin among 7, 872 patients with head and neck cancer, we found a modest protective association between metformin exposure and all‐cause mortality in the 2‐year post‐diagnosis period.